Simplikasi Birokrasi melalui Birokrasi Agile - Neolaka, Melkisedek N.B.C (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2024)
In the digital era which is fast-paced, dynamic and always changing, according to Weber's view, the traditional bureaucratic approach seems slow and rigid in responding to change. In this condition, bureaucratic simplification is an offer to the government to increase efficiency, transparency and quality of public services. The government is expected to creatively innovate to find a bureaucratic model that is more adaptive and responsive to dynamics and changes in the internal and external environment. Responding to this situation, agile bureaucracy is a solution offering to simplify bureaucratic processes, by applying the principles of flexibility, collaboration and fast decision making. In this case, the existence of an agile bureaucracy is expected to motivate the bureaucracy to adapt more quickly to change, increase innovation and provide better public services. This article examines the concept of agile bureaucracy, its implementation strategy, as well as the challenges and opportunities faced in efforts to simplify bureaucracy in Indonesia. By adopting an agile approach, the government is expected to be able to create a bureaucracy that is leaner, more dynamic and ready to face future challenges.